2013
DOI: 10.1002/ajmg.a.36029
|View full text |Cite
|
Sign up to set email alerts
|

Increased fracture risk and low bone mineral density in patients with loeys–dietz syndrome

Abstract: Loeys-Dietz syndrome is a recently recognized connective tissue disorder with widespread systemic involvement. Little is known about its skeletal phenotype. Our goal was to investigate the risk of fracture and incidence of low bone mineral density in patients with Loeys-Dietz syndrome. We performed a cross-sectional, descriptive, survey-based study with subsequent chart review from July 2011 to April 2012. Fifty-seven patients (26 men, 31 women) with Loeys-Dietz syndrome confirmed by genetic testing completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The surgical approaches and postoperative complications in our cohort reflect the bone fragility previously reported in Loeys-Dietz syndrome [23][24][25] . Although it is unclear specifically how aberrant TGF-b signaling affects bone development, it is speculated that it causes uncoupling of bone formation and resorption 25,26 . Pseudarthrosis and failure of fixation were particularly common complications and may reflect defects in bone mineralization and resorption 25 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The surgical approaches and postoperative complications in our cohort reflect the bone fragility previously reported in Loeys-Dietz syndrome [23][24][25] . Although it is unclear specifically how aberrant TGF-b signaling affects bone development, it is speculated that it causes uncoupling of bone formation and resorption 25,26 . Pseudarthrosis and failure of fixation were particularly common complications and may reflect defects in bone mineralization and resorption 25 .…”
Section: Discussionsupporting
confidence: 54%
“…Although it is unclear specifically how aberrant TGF-b signaling affects bone development, it is speculated that it causes uncoupling of bone formation and resorption 25,26 . Pseudarthrosis and failure of fixation were particularly common complications and may reflect defects in bone mineralization and resorption 25 . Other common postoperative complications, including junctional kyphosis and instability, are likely the result of ligamentous laxity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LDS have a higher incidence of fractures. A study by Sponseller and colleagues 54 of individuals with LDS 1/2 revealed a 50% risk of fracture by 14 years of age. Limited dual-energy X-ray absorptiometry data supported the findings, revealing that at least 60% of patients had low or very low bone mineral density in the spine, hip, and/or femoral neck.…”
Section: Clinical Manifestations and Management Recommendations By Omentioning
confidence: 98%
“…Polymorphisms in BMP2 and BMP4 are also linked to osteoporosis, low bone mineral density, and fragility fracture risk (Styrkarsdottir et al 2003;Ramesh Babu et al 2005), although a correlation between a SNP in BMP2 and osteoporosis remains to be confirmed (Medici et al 2006). Osteoporosis, which presents with a high risk of pathologic fractures and delayed bone healing, is also a feature of LDS, and appears to be particularly frequent and most severe in patients with heterozygous missense mutations in TGFBR1 or TGFBR2 (Kirmani et al 2010;Tan et al 2013). Given the dual roles of TGFb signaling in bone formation and resorption, and the paradoxical effects of LDS mutations on TGF-b signaling in vivo, the mechanisms leading to osteoporosis in LDS remain unclear.…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 99%